Associations between psychedelic use and adverse outcomes in substance use disorders: a real-world EHR-based cohort study - Qeadan, Fares; McCunn, Ashlie; Tingey, Benjamin; Thielking, Paul (Frontiers in Psychiatry, 2025)
AimsTo examine associations between psychedelic use and adverse health outcomes, including overdose, relapse, mental health crises, and hospitalizations, among individuals with substance use disorders (SUD), and to compare these outcomes across different treatment modalities including anesthetics and outpatient SUD services.DesignRetrospective cohort study using propensity score-weighted quasi-Poisson regression models to estimate adjusted incidence rate ratios (aIRRs).SettingData were drawn from Oracle EHR Real-World Data™ comprising 138 U.S. health systems restricted to those ≥12 years old from January 1, 2000, to August 31, 2023.Participants3,209,798 patients with a documented SUD diagnosis from 2000 to 2023. Patients with a prior history of psychedelic use or hallucinogen-related diagnoses were excluded. The final cohort included 8,514 new psychedelic users and over 3.2 million non-users.MeasurementsExposures were captured during a 3-month post-index period and included outpatient psychedelic prescriptions or procedures (primarily ketamine), general anesthetic outpatient prescriptions, and outpatient SUD services. Outcomes, assessed over 2 years, included SUD-related hospitalizations/emergency department (ED) visits, mental health crises, all-drug overdoses, and relapse. Propensity scores accounted for demographic, clinical, and behavioral confounders.FindingsPsychedelic use was associated with significantly reduced rates of all adverse outcomes, including all-drug overdose (aIRR F;= F;0.48; 95% CI: 0.37-0.63), relapse (aIRR F;= F;0.68; 0.60-0.77), SUD hospitalizations/ED visits (aIRR F;= F;0.76; 0.69-0.82), and mental health crises (aIRR F;= F;0.82; 0.73-0.92), compared to no treatment. The combination of psychedelics, anesthetics, and outpatient services was associated with the strongest reduction in mental health crises (aIRR F;= F;0.21; 0.06-0.77). Trends were consistent in sensitivity analyses including patients with mental health conditions and comparisons to medication-assisted treatment.ConclusionsIn this large national cohort, psychedelic use, particularly when combined with anesthetic and outpatient care, was associated with reduced adverse health outcomes among people with SUD. These findings support further investigation into psychedelic-based interventions within integrated treatment frameworks.